Alih Kode dalam Komunikasi Verbal pada Mahasiswa Semester V Program Studi Pendidikan Bahasa dan Sastra Indonesia, Universitas Flores Ende - Zaenab Jamaludin; Maria Floriana Serlin (Universitas Muhammadiyah Mataram, 2023)
This study aims to (1) find and describe the form of code switching in the verbal communication of fifth semester students of the Indonesian Language and Literature Education Study Program, University of Flores for the 2022/2023 academic year, (2) find and describe the function of code switching in Verbal communication of fifth semester students of the Indonesian Language and Literature Education Study Program, University of Flores, for the 2022/2023 academic year, found and described the meaning of code switching in the verbal communication of fifth semester students of the Indonesian Language and Literature Education Study Program, University of Flores, for the 2022/2023 academic year.The approach used in this study is qualitative with the technique used is non-statistical because in analyzing it does not use numbers. While the theory used is Sociolinguistics and Bilingualism theory especially about code switching. The results of data analysis show that in the student communication process there is code switching used by fifth semester students of the Indonesian Language and Literature Education Study Program at the University of Flores for the 2022/2023 academic year divided into two, namely: (1) code switching from Indonesian to regional languages and ( 2) code switching from regional languages to Indonesian.